Response sensitivity to bacteriophages of Staphylococcus aureus strains isolated from the microbiota of the oropharynx in children of Irkutsk - E. V. Grigorova (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
Dysbiotic disorders of the oropharynx takes one of the first places in the structure of morbidity worldwide. The aim of the study was to determine the peculiarities of microbiocenosis of the oropharynx in children at different ages and to assess the level of sensitivity of S. aureus strains to specific bacteriophages. Material for the study consisted of 84 smears from the oropharynx of children with inflammatory diseases of the upper respiratory tract (nasopharyngitis, pharyngitis, tonsillitis, laryngitis (J00, J02, J03, J04 according to 1CD-10). The biological material was distributed depending on the age of the surveyed: the first group - children 3-6 years (n = 61) and the second age group - children 7-12 years (n = 23). Studies of the microflora of the oropharynx were performed according to standard methods. Isolated microorganisms were identified by morphological, tinctorial, cultural and biochemical properties. The results were evaluated in accordance with the Order of USSR Ministry of Health N 535 as of April 22,1985. Specific lytic activity of bacteriophages against S. aureus was determined using preparations of staphylococcal bacteriophage and polyvalent pyobacteriophage Sexta. The sensitivity of strains of S. aureus to specific bacteriophages was assessed by the method of «crosses», according to the guidelines. Statistical analysis was performed with the use of licensed applications Offiœ Ms Excel 2007for Windows 7 BioStat v. 5.0.1.2008. Correlation analysis (Pearson method) was used. 1t has been shown that with increasing age children in the oropharynx microbial density is increasing for indicators of both normoflora (S. oralis), and of opportunistic microflora (S. β-hemolytic, S. pyogenes, S. pneumoniae, bacteria Enterobacteriaceae), especially of S. aureus (up to 74 %). Registration of sensitive strains of S. aureus in more than 70 % of cases in preschool and school-aged children is evidence of the correctness of correction of the dysbiotic disorders of the oropharynx with the use of bacteriophages of staphylococcus and Sexta.